When to consider cardiac MRI in the evaluation of the competitive athlete after SARS-CoV-2 infection - Phelan, D.; Kim, J. H.; Drezner, J. A.; Elliott, M. D.; Martinez, M. W.; Chung, E. H.; Krishan, S.; Levine, B. D.; Baggish, A. L. (British Journal of Sports Medicine, 2022)
Uncertainty regarding the prevalence and clinical implications of myocarditis in athletes after SARS-CoV-2 infection prompted sports medicine and sports cardiology physicians to develop new return-to-play protocols early in the pandemic.1 2 Concern that exercise may exacerbate the severity of cardiac injury and increase the risk of arrhythmic death in those with viral-related myocarditis led to recommendations for more intensive cardiac testing in athletes following SARS-CoV-2 infection, usually, in the USA, with some combination of a resting 12-lead ECG, troponin and transthoracic echocardiogram (so-called `triad` testing). Based solely on expert opinion and rapidly evolving clinical experience, these initial recommendations emphasised the need to gather high-quality data to guide future recommendations.1 2 Early-case series documenting local experiences with cardiac MRI (CMR) in asymptomatic and mildly symptomatic athletes reported high frequencies of cardiac injury.3 These data factored heavily in decisions about restarting sports and even led one sports conference within the National Collegiate Athletic Association to mandate all athletes, whether symptomatic or not, be screened with a CMR.